DESCRIPTIVE ART HIS WORKS PSYCHOLOGICAL ANALYSIS TO DO - Tuliyeva Ruxsora (Ethiopian International Journal of Multidisciplinary Research, 2025)
This article figurative art his works psychological analysis to do learns . In the article art and psychology between mutual connection , figurative art his works psychological in terms of analysis to do and colors , composition and forms such as of elements content discussion Also , art​​ works human internal state of mind , mood reflection provider tool as seeing will be issued . This research of artists-creators his works further deeper understanding and their the essence to understand help is given .